An experimental study on the rehabilitation performance of CFRP-strengthened bubble deck slabs: effects of void size and preloading levels (Fracture and Structural Integrity, 2025)
This study examines the rehabilitation performance of reinforced concrete bubble deck slabs (with 50 mm and 60 mm voids) strengthened with externally bonded CFRP sheets. Nine specimens were tested: eight bubble slabs (grouped by void size and preloading level) and one solid control slab. Three specimens of each void size were pre-damaged to 50%, 60%, and 75% of their ultimate load before being strengthened with CFRP and retested. One specimen per group remained unstrengthened for comparison. Results show that increasing void size reduces load capacity: the unstrengthened 50 mm and 60 mm void slabs achieved 96.2% and 86.5% of the solid slab’s strength, respectively. CFRP rehabilitation effectively restored structural performance, with 50 mm void slabs recovering up to 98.5% of the control slab’s capacity and exhibiting 25% lower deflection. In contrast, 60 mm void slabs showed lower recovery efficiency, particularly at higher preloading levels SB-6-75 recovered only 82.5% of the control strength. All strengthened specimens failed by CFRP debonding combined with flexural cracking, with no shear failures observed. The study demonstrates that CFRP retrofitting significantly enhances the strength and stiffness of damaged bubble deck slabs, especially those with smaller voids. Void size and pre-damage level are critical factors influencing rehabilitation success.
Keywords: Rehabilitation; Damaged; Two-way slab; , CFRP sheets; Bubbled slab